STRATEGI SUSTAINABILITY BUSINESS UMKM KULINER MENGGUNAKAN SHOPEEFOOD DAN GOJEK TERHADAP TINGKAT PENDAPATAN - Putri Br Sembiring; Pudjihardjo (Journal of Development Economic and Social Studies, 2024)
This research aims to analyze the effect of capital, working hours, labor, and length of business period on the income level of culinary UMKM on Sigura-Gura Street, Malang City and the sustainability business strategy using shopeefood and gojek. This study uses descriptive quantitative methods, the data sources in this study are primary data obtained directly from the respondents and secondary data derived from several literatures. A research sample of 50 respondents based on Roscoe's theory, the respondents are culinary UMKM registered at Shopee Food and Gojek which are on Jalan Sigura-Gura. The independent variables that affect income according to the theory of production are capital variables (X1), working hours (X2), labor (X3), length of business (X4). While the dependent variable is Culinary UMKM Income (Y). Research data analysis method with Multiple Regression, Classical Assumption Test and Hypothesis Testing.